Effects of prolonged drought on the anatomy of sun and shade needles in young Norway spruce trees. Issue 21 (15th October 2015) - Gebauer, Roman; Volařík, Daniel; Urban, Josef; Børja, Isabella; Nagy, Nina Elisabeth; Eldhuset, Toril Drabløs; Krokene, Paal
Abstract: Predicted increases in the frequency and duration of drought are expected to negatively affect tree vitality, but we know little about how water shortage will influence needle anatomy and thereby the trees' photosynthetic and hydraulic capacity. In this study, we evaluated anatomical changes in sun and shade needles of 20‐year‐old Norway spruce trees exposed to artificial drought stress. Canopy position was found to be important for needle structure, as sun needles had significantly higher values than shade needles for all anatomical traits (i.e., cross‐sectional needle area, number of tracheids in needle, needle hydraulic conductivity, and tracheid lumen area), except proportion of xylem area per cross‐sectional needle area. In sun needles, drought reduced all trait values by 10–40%, whereas in shade needles, only tracheid maximum diameter was reduced by drought. Due to the relatively weaker response of shade needles than sun needles in drought‐stressed trees, the difference between the two needle types was reduced by 25% in the drought‐stressed trees compared to the control trees. The observed changes in needle anatomy provide new understanding of how Norway spruce adapts to drought stress and may improve predictions of how forests will respond to global climate change. Abstract : In our study we found that sun needles had significantly higher values than shade needles for all anatomical traits. In sun needles drought reduced all trait values, whereas in shade needles only tracheid maximum diameter was reduced by drought. The observed changes in needle anatomy provide new understanding of how Norway spruce adapts to drought stress and may improve predictions of how forests will respond to global climate change.